L’éphémère est éternel. Les arts vivants au Centre Pompidou (1977-1987) - Marion Boudier; Linus Gratte (In Situ)
In this article, we would like to share a discussion about the processes of inventory and analysis currently underway on the archives of the performing arts at the Pompidou Centre in Paris. This work, initiated by the authors of the present article, is being carried out under the auspices of the Laboratoire d’histoire permanente (LHP), a laboratory for permanent history at the Pompidou centre, run by Antoine de Baecque from 2022 to 2024. It concentrates on the centre’s first ten years from 1977 to 1987. The ambition of the Pompidou Centre at the time of its creation in 1977 was, in the words of its first president Robert Bordaz “to unite realities that historical evolution, over time, has separated by diversification and specialisation.” By means of ‘polyvalence’ and ‘interdisciplinarity’, the brand-new museum and cultural institution was expected to reassociate ‘theatrical research’ with music, poetry, architecture, sculpture and painting, in the hope of “reinserting art and culture into the tissues of life.” And indeed, the Centre’s early years offer a varied programme of the performing arts, underlining the place’s experimental vocation and its ambition to make creative work resonate with the innovative architecture of the building. Next to those of choreographers and performance artists works were presented by playwrights and theatrical creators such as Lucien Attoun’s Théâtre Ouvert or Antoine Vitez, or the pluri-disciplinary spectacle entitled ‘The ephemeral is eternal’, by Claude Confortès and Elsa Wolliaston, based on a text by Michel Seuphor with sets inspired by Piet Mondrian. The spectacles were all exploratory ventures, leaving archival traces or ‘signs of loss’ (Georges Banu). The analysis of this intense activity in the field of the performing arts reveals ‘hegemonic structures’ (Anne Bénichou) which are an invitation to question the place of the performing arts within the new museum and cultural institution and the possible ways of preserving a heritage of these performing arts.